(untitled) (Damu Journal of Sport Sciences, 2025)
This study included an analysis of the reality of sports investment in Najaf Club in light of the developments taking place in the field of sports investment. The analysis focused on three main axes: first، the legal system in force; second، the suitability of the environment for investment; and third، the ability of the administrative staff and human resources to keep pace with، accept، and benefit from investors. The study reached conclusions through the researcher's use of a descriptive approach using a survey method and correlational relationships، as appropriate for the nature of the study. The research sample included (199) administrators، businessmen، players، and fans to measure sports investment in Najaf Club. The scale was prepared and applied to the sample. The research yielded a set of conclusions، including: The reality of sports investment in Najaf Club suffers from The shortcomings of the relevant authorities، and the lack of a clear vision and sufficient experience in the laws and regulations governing sports investment، are among the most important recommendations: Administrative bodies should coordinate and unify collective efforts among their members in administrative investment work to achieve the goals، as well as seek the assistance of specialists from among economists to present a feasibility study on the reality of sports investment. The media must play its role in encouraging and educating the public on the importance of sports investment.